A New Technique for Verifying the Consistency of Distributed R-Trees - de Oliveira, Sávio S. T.; Filho, José F. de S.; Rodrigues, Vagner J. do Sacramento; Cardoso, Marcelo de C.; Carvalho, Sérgio T. (Journal of Information and Data Management, 2015)
The ever-increasing of the large spatial datasets and the widely application of the complex computation have motivated the emergence of distributed algorithms to process spatial operations efficiently. The R-tree index is broadly used by researches as a distributed spatial structure for indexing and retrieval of spatial objects. However, a big challenge has arisen, that is, how to check the consistency of distributed R-Trees. In the past few years researches have been published on both distributed R-Tree and verification of distributed systems. Though none of them has proposed a technique to check the consistency of distributed R-Trees. This article presents a new approach for verifying the consistency of distributed R-Trees, which is called RConsistency. It allows collect information about the distributed R-Tree once it has been created. RConsistency also collects information about the distribute R-Tree and can helps to reduce the overlapping and dead area. It can be used with any index similar to R-Tree, since the RConsistency algorithm uses the nodes organization of the R-Tree to collect consistency information. The algorithm was used on DistGeo, a platform to process distributed spatial operations. A graphic tool, named RConsistency Visualizer, was developed to show the output of the RConsistency algorithm.